2019
DOI: 10.1108/gkmc-10-2018-0083
|View full text |Cite
|
Sign up to set email alerts
|

Computer self-efficacy as a predictor of undergraduates’ use of electronic library resources in federal universities in South-west Nigeria

Abstract: Purpose Undergraduates use electronic library resources for academic activities. However, literature has revealed that undergraduates’ use of electronic library resources is low in Nigeria owing to attitude, computer literacy and information retrieval skills, while little attention was given to computer self-efficacy. This paper aims to examine computer self-efficacy as a predictor of undergraduates’ use of electronic library resources in federal universities in south-west Nigeria. Design/methodology/approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…The findings of our study corroborates the findings of a recent study by Ebijuwa and Mabawonku (2019) that e-thesis and the OPAC were more frequently used on daily basis than e-books, e-journals and databases. The finding also confirmed the findings of Madhusudhan's (2010) study that most (62 per cent) students used eresources on a daily basis.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 91%
See 2 more Smart Citations
“…The findings of our study corroborates the findings of a recent study by Ebijuwa and Mabawonku (2019) that e-thesis and the OPAC were more frequently used on daily basis than e-books, e-journals and databases. The finding also confirmed the findings of Madhusudhan's (2010) study that most (62 per cent) students used eresources on a daily basis.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 91%
“…Ukachi et al (2014) observed that eresources are not adequately used by undergraduate students who have a negative attitude towards its use because they feel they are computer illiterates. The study by Ebijuwa and Mabawonku (2019) revealed that the level of undergraduates' computer selfefficacy was high. The researchers found that computer self-efficacy influenced undergraduates' use of electronic library resources in federal universities in South West Nigeria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adetomiwa and Okwilagwe (2018) identified significant positive correlation between awareness and use of electronic databases. In another recent paper, Ebijuwa and Mabawonku (2019) found significant relationship existed between computer self-efficacy and use of electronic library resources. Other authors (see, for example, Yusoff et al , 2009; Ahmed, 2013a) identified demographic characteristics such as gender, academic status, knowledge of the search domain, etc.…”
Section: Introductionmentioning
confidence: 94%
“…The superiority of information retrieval through digital technologies depends on the quality of the ICT skills of the user (Habiba & Ahmed, 2020). For the users of the university library to be effective on the utilization of e-resources they must be in a position to locate, access, evaluate, and use library information sources in several formats for academic or other uses such as social and global (Ebijuwa & Mabawonku, 2019). Habiba and Ahmed (2020) believe that ICT skills are necessary for managing, assessing, and using electronic resources for research, term papers, decision making, and solving problems.…”
Section: Literature Reviewmentioning
confidence: 99%